The quest for Noah's ark - Montgomery, John Warwick (Minneapolis, MN Bethany Fellowship, 1972)
Includes bibliographical references indexes, and photographs.
Keywords: Bible. O.T. Genesis -- criticism, interpretation, etc; Deluge -- evidence